Cenozoic tectonic reactivation and its implications for landscape transience in southeastern Brazil - dos Santos, Jéssica Miranda; Salamuni, Eduardo; Val, Pedro; da Silva, Clauzionor Lima; Morales, Norberto [UNESP]; de Souza, Iata Anderson [UNESP]; Sanches, Emerson (Wiley, 2023)
Intraplate settings far from tectonic plate boundaries are normally thought to be tectonically inactive regions in which the landscape evolves via the slow downcutting of fluvial systems. When identified, tectonic reactivations are thought to be of too low an amplitude and not cause any change in the landscape. However, in the absence of datable markers of tectonic deformation, the landscape can be used as a passive marker of intraplate tectonic activity. In this study, we investigate the northern boundary of the Ponta Grossa Arch in the southeastern portion of the Brazilian passive margin. We mapped and studied the spatial and temporal (relative) relationships between brittle structures and geomorphic markers of base level changes. Drainage anomalies (knickpoints and high ksn values) are correlated with structural/tectonic lineaments in which we recognize strike-slip and transtensional faults with right-lateral and left-lateral kinematics. Through mapping and analysis of structural data, we constrained the underlying structural framework. The fault data demonstrate the counterclockwise rotation of the maximum stress field, which moved from the NE–SW orientation (at the Cretaceous-Paleogene boundary) to N-S to reach the current WNW-ESE position. Together, the data suggest that, though subtle and low-magnitude, the evolution of intraplate stress field forms a dynamic forcing of intracontinental landscape change.
Keywords: Ponta Grossa Arch; tectonic pulses; tectonic reactivations